Plasma rico em plaquetas (PRP) aplicado na artroplastia total do joelho - Guerreiro, João Paulo Fernandes; Danieli, Marcus Vinicius; Queiroz, Alexandre Oliveira; Deffune, Elenice [UNESP]; Ferreira, Rosana Rossi [UNESP] (Thieme, 2014)
Objective: To evaluate the efficacy of platelet-rich plasma regarding healing, pain and hemostasis after total knee arthroplasty, by means of a blinded randomized controlled and blinded clinical study. Methods: Forty patients who were going to undergo implantation of a total knee prosthesis were selected and randomized. In 20 of these patients, platelet-rich plasma was applied before the joint capsule was closed. The hemoglobin (mg/dL) and hematocrit (%) levels were assayed before the operation and 24 and 48hours afterwards. The Womac questionnaire and a verbal pain scale were applied and knee range of motion measurements were made up to the second postoperative month. The statistical analysis compared the results with the aim of determining whether there were any differences between the groups at each of the evaluation times. Results: The hemoglobin (mg/dL) and hematocrit (%) measurements made before the operation and 24 and 48hours afterwards did not show any significant differences between the groups (p > 0.05). The Womac questionnaire and the range of motion measured before the operation and up to the first two months also did not show any statistical differences between the groups (p > 0.05). The pain evaluation using the verbal scale showed that there was an advantage for the group that received platelet-rich plasma, 24hours, 48hours, one week, three weeks and two months after the operation (p < 0.05). Conclusions: In the manner in which the platelet-rich plasma was used, it was not shown to be effective for reducing bleeding or improving knee function after arthroplasty, in comparison with the controls. There was an advantage on the postoperative verbal pain scale.

Objetivos: Avaliar, por meio de um estudo clínico, randomizado, controlado e cego, a eficácia do plasma rico em plaquetas na cicatrizac¸ão, dor e hemostasia após artroplastia total do joelho. Métodos: Foram selecionados 40 pacientes que seriam submetidos a prótese total do joelho e randomizados. Em 20 desses pacientes foi aplicado o plasma rico em plaquetas antes do fechamento da cápsula articular. Foram feitas dosagens de hemoglobina (mg/dL) e hemató- crito (%) no pré-operatório, após 24 e 48 horas da cirurgia. Foram aplicados o questionário Womac e a escala verbal da dor e medidas as amplitudes de movimento do joelho até o segundo mês pós-operatório. A análise estatística comparou os resultados a fim de comprovar haver diferenc¸a entre os grupos em cada um dos momentos da avaliac¸ão. Resultados: Medidas do valor da hemoglobina (mg/dL) e hematócrito (%) feitas no pré- -operatório, após 24 e 48 horas da cirurgia, não mostraram diferenc¸as significativas entre os grupos (p > 0,05). O questionário Womac e a amplitude de movimento medida no pré- -operatório e até os dois primeiros meses também não mostraram diferenc¸as estatísticas entre os grupos (p > 0,05). A avaliac¸ão da dor por meio da escala verbal mostrou vantagem no grupo que usou o plasma rico em plaquetas após 24 e 48 horas, uma e três semanas e dois meses de pós-operatório (p < 0,05). Conclusões: Da maneira com que foi usado, o plasma rico em plaquetas não se mostrou efetivo para reduzir sangramento ou melhorar a func¸ão do joelho após a artroplastia em comparac¸ão com os controles. Houve vantagem na escala verbal de dor pós-operatória.
Platelet-rich plasma (PRP) applied during total knee arthroplasty
Keywords: Arthroplasty; Knee; Transfusion; Platelet-rich plasma; Hemorrhage; Artroplastia; Joelho; Transfusão; Plasma rico em plaquetas; Hemorragia